Dermal papilla cells and melanocytes response to physiological oxygen levels depends on their interactions. (8th June 2021) - Abreu, Carla M.; Reis, Rui L.; Marques, Alexandra P.
Abstract: Background: Human dermal papilla (DP) cells and melanocytes (hMel) are central players in hair growth and pigmentation, respectively. In hair follicles (HFs), oxygen (O2 ) levels average 5%, being coupled with the production of reactive oxygen species (ROS), necessary to promote hair growth. Materials and Methods: DP cell and hMel proliferation and phenotype were studied under physiological (5%O2, physoxia) or atmospheric (21%O2, normoxia) oxygen levels. hMel‐DP cells interactions were studied in indirect co‐culture or by directly co‐culturing hMel with DP spheroids, to test whether their interaction affected the response to physoxia. Results: Physoxia decreased DP cell senescence and improved their secretome and phenotype, as well as hMel proliferation, migration, and tyrosinase activity. In indirect co‐cultures, physoxia affected DP cells' alkaline phosphatase (ALP) activity but their signalling did not influence hMel proliferation or tyrosinase activity. Additionally, ROS production was higher than in monocultures but a direct correlation between ROS generation and ALP activity in DP cells was not observed. In the 3D aggregates, where hMel are organized around the DP, both hMel tyrosinase and DP cells ALP activities, their main functional indicators, plus ROS production were higher in physoxia than normoxia. Conclusions: Overall, we showed that the response to physoxia differs according to hMel‐DP cells interactions and that the microenvironment recreated when in direct contact favours their functions, which can be relevant for hair regeneration purposes. Abstract : Under physiological oxygen levels (5% O2, physoxia), both the highly specialized human dermal papilla (DP) cells and melanocytes (hMel) show increased proliferative capacity and functionality than under atmospheric oxygen levels (21% O2 ). Interestingly, DP cells and hMel response to physoxia varied not only if in co‐culture, but also whether they were interacting indirectly or directly. When hMel and DP cells were directly contacting in organized 3D cell aggregates that better resembled the HF microarchitecture and respective phenotype, the microenvironment recreated under physoxia better favoured their highly specialized functions.